If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + 4) = -21 Reorder the terms: 3(4 + a) = -21 (4 * 3 + a * 3) = -21 (12 + 3a) = -21 Solving 12 + 3a = -21 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3a = -21 + -12 Combine like terms: 12 + -12 = 0 0 + 3a = -21 + -12 3a = -21 + -12 Combine like terms: -21 + -12 = -33 3a = -33 Divide each side by '3'. a = -11 Simplifying a = -11
| 15x=0.3 | | -9.2i-7.88=1.1i+9.39 | | 5.5x+13=200 | | -8=0+b | | 8x+2=3x+37 | | 3/7z=-3/8 | | 6.2(x+-3)+-4.2=33 | | 9m+10-14m=15 | | 6*9-6/2 | | 16x(36/9 | | x/-18.3=-5 | | 24a+3(2a-5)=51 | | 8/16b-4/16b | | 5x9-6/2 | | -12x+-1y=21 | | 9-5x=2x-19 | | y=(0.0025s^2+0.05s+1)(s^2+31.5s+250)+0.39 | | h=66+173t+-16t^2 | | 2/3r=1/5 | | -8.3-(-3.7)+5.2= | | y-19.6=56 | | 5-x(4+7)=35 | | y^2+10y+x+27=0 | | 95000/6 | | 5-2y=37 | | 23+y=-19 | | h=-16t^2+173t+66 | | x^2+2y^2=576 | | (5x-3)(6x-9)= | | -15+3x=-6y | | 5+nover-3=14 | | 34=9-34 |